2022
DOI: 10.1038/s41598-022-22547-9
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model for hospitalization and survival to COVID-19 in a retrospective population-based study

Abstract: The development of tools that provide early triage of COVID-19 patients with minimal use of diagnostic tests, based on easily accessible data, can be of vital importance in reducing COVID-19 mortality rates during high-incidence scenarios. This work proposes a machine learning model to predict mortality and risk of hospitalization using both 2 simple demographic features and 19 comorbidities obtained from 86,867 electronic medical records of COVID-19 patients, and a new method (LR-IPIP) designed to deal with d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
1
13
2
Order By: Relevance
“…In a predictive model examining the survival of COVID-19 patients, we found OA to be a predictor associated with this model, which drew our attention ( 11 ). Therefore, to investigate the potential link between COVID-19 and OA, we researched all the literature related to COVID-19 and OA and found that most studies focused on changes in treatment, diagnosis, and recovery status of OA patients during COVID-19 isolation ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a predictive model examining the survival of COVID-19 patients, we found OA to be a predictor associated with this model, which drew our attention ( 11 ). Therefore, to investigate the potential link between COVID-19 and OA, we researched all the literature related to COVID-19 and OA and found that most studies focused on changes in treatment, diagnosis, and recovery status of OA patients during COVID-19 isolation ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 92%
“…In a predictive model examining the survival of COVID-19 patients, we found OA to be a predictor associated with this model, which drew our attention ( 11 ). Interestingly, Paxlovid, a drug widely used to treat COVID-19, has been shown to accelerate cartilage degeneration in patients, thereby triggering or exacerbating osteoarthritis ( 12 ).…”
Section: Introductionmentioning
confidence: 92%
“…Even though there is considerable heterogeneity among COVID-19 mortality prediction models, our findings regarding asthma as a strongly predictive COVID-19 mortality factor should be interpreted with caution. In fact, in studies where asthma was not predictive of mortality, intravenous corticosteroids, vasopressors, oxygen, and intubation were commonly used in ICU patients (Banoei et al, 2021 ; Cisterna-García et al, 2022 ). Another plausible explanation is that female gender was a significant predictor of mortality in our study, and asthma deaths in the ICU are strongly associated with women, specifically those admitted for COVID-19 in the ICU (Pennington et al, 2019 ; Beurnier et al, 2020 ; Ren et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple comorbidities and advanced age are independent risk factors for mortality in COVID-19 patients [ 19 ]. The CCI is a well-validated, simple, easy-to-use index for assessing the prognosis and survival of COVID-19 patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%